Protocol for assessing immune-target cell interactions using a single-cell cytotoxicity assay - Zhihao Wei; Konglan Lin; Min Huang; Shicheng Su; Yiwen Lu (STAR Protocols)
Summary: Standard flow cytometry-based assays can determine the cytotoxicity of immune effector cells, but it is challenging to monitor the dynamic processes of cytotoxicity. Here, we present a protocol for continuous observation of natural killer (NK) cell-mediated cytotoxicity with microwell arrays using an automated microscope. We describe steps for isolating and labeling primary NK cells, loading cells onto microwell arrays, monitoring target wells, and image analysis. This protocol facilitates observation of the dynamics of immune-target cell interactions at the single-cell level.For complete details on the use and execution of this protocol, please refer to Li et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.